Exploring the impact of the Liberia Land Rights Act of 2018 on the improvement of women’s land rights : case study in Grand Bassa County, Wee Statutory District. - Wegerif, Marc (University of Pretoria, 2025)
Dissertation (MSc (Development Studies))--University of Pretoria, 2024.